More bang for your monitoring bucks: Detection and reporting of non-indigenous species. Issue 1 (15th May 2015) - Whomersley, P.; Murray, J.M.; McIlwaine, P.; Stephens, D.; Stebbing, P.D.
Highlights: Addressing principals highlighted in current national and international policy. Data collected for other purposes can be utilised to address additional policy needs. Monitoring programmes could be developed with sufficient coordination and management. Abstract: 'Collect once, use often' is a frequently cited principle in both national and international efforts to promote the collection, archiving and sharing of marine monitoring data. Since the implementation of the Marine Conservation Zone (MCZ) evidence collection programme, 67 recommended MCZ sites have been visited and a suite of marine data collected. Here we present how this dataset was utilised outside of the MCZ programme to identify occurrences of non-indigenous species (NIS) around the UK coast. One hundred and thirty-five aquatic species from the Non-native Species Information Portal (NNSIP) register were used to produce a standard list of NIS against which, infauna and epifaunal data records from the MCZ project were compared. A total of 20 NIS were identified across 42 of the 67 sites surveyed. This study demonstrates that with sufficient coordination and management data collected for other purposes can be easily utilised to address additional policy requirements.